One-year retention of gait speed improvement in stroke survivors after treatment with a wearable home-use gait device - Darcy, Brianne; Rashford, Lauren; Tsai, Nancey T.; Huizenga, David; Reed, Kyle B.; Bamberg, Stacy J. M. (Frontiers in Neurology, 2024)
Background: Gait impairments after stroke are associated with numerous physical and psychological consequences. Treatment with the iStrideTM gait device has been shown to facilitate improvements to gait function, including gait speed, for chronic stroke survivors with hemiparesis. This study examines the long-term gait speed changes up to twelve months after treatment with the gait device. Methods: Eighteen individuals at least one-year post-stroke completed a target of 12, 30-minute treatment sessions with the gait device in their home environment. Gait speed was measured at baseline and five follow-up sessions after the treatment period: one week, one month, three months, six months, and twelve months. Gait speed changes were analyzed using repeated-measures ANOVA from baseline to each follow-up time frame. Additional analysis included comparison to the minimal clinically important difference (MCID), evaluation of gait speed classification changes, and review of subjective questionnaires. Results: Participants retained an average gait speed improvement > 0.21 m/s compared to baseline at all post-treatment time frames. Additionally, 94% of participants improved their gait speed beyond the MCID during one or more post-treatment measurements, and 88% subjectively reported a gait speed improvement. Conclusion: Treatment with the gait device may result in meaningful, long-term gait speed improvement for chronic stroke survivors with hemiparetic gait impairments.